Проблеми оперативного виявлення і реагування на інциденти інформаційної безпеки - Ушатов, В.; Сєвєрінов, О. В. (ХНУРЕ, 2019)
The issues of the effective use of information protection and event management systems are considered. The analysis of the problems arising when using these systems in organizations is carried out. Possible solutions to these problems used in the latest versions of SIEM systems are considered.
Keywords: управління інформаційною безпекою; інциденти інформаційної безпеки; SIEM